2022
DOI: 10.3389/fpubh.2022.901680
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Prognostic Factor and a Novel Dynamic Prediction Model for Overall Survival of Elderly Patients With Chondrosarcoma: A Population-Based Study

Abstract: BackgroundChondrosarcoma is the most common primary bone sarcoma among elderly population. This study aims to explore independent prognostic factors and develop prediction model in elderly patients with CHS.MethodsThis study retrospectively analyzed the clinical data of elderly patients diagnosed as CHS between 2004 and 2018 from the Surveillance, Epidemiology, and End Results (SEER) database. We randomly divided enrolled patients into training and validation group, univariate and multivariate Cox regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Metastasis is considered one of the most notable prognostic indicators of POSNs, and it is incorporated into almost all previously reported prognostic models established for patients with initially diagnosed POSNs (19,20). Not only in POSNs but also in other malignancies, as soon as patients develop metastatic disease, their survival rate will drop dramatically compared with their counterparts without DM (24)(25)(26). In the present study, 238 (17.70%) cases were confirmed to have distant organ metastasis at the time of initial diagnosis, as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is considered one of the most notable prognostic indicators of POSNs, and it is incorporated into almost all previously reported prognostic models established for patients with initially diagnosed POSNs (19,20). Not only in POSNs but also in other malignancies, as soon as patients develop metastatic disease, their survival rate will drop dramatically compared with their counterparts without DM (24)(25)(26). In the present study, 238 (17.70%) cases were confirmed to have distant organ metastasis at the time of initial diagnosis, as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…All of our data were downloaded from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) database via SEER Stat 8.4.1. 1 The database is currently the largest and publicly available cancer database, containing 18 cancer registries covering approximately 28% of the United States population ( 17 ). The SEER database started recording complete cancer metastasis sites from 2010 and for patients to have sufficient follow-up time records, so we selected all KC patient data from 2010 to 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, the American Joint Committee on Cancer (AJCC) tumor node metastasis TNM staging system, incorporated with the anatomical information of the extent of the primary tumor (T), regional lymph nodes (N), and distant metastases (M), is widely used to assess the prognosis of cancer patients. Although the TNM staging system is considered as standard protocol for prognosis evaluation for patients with malignancies, several studies have shown that the current TNM staging system for STS patients is inadequate in regard to the correctness of N staging and individualized variability ( 9 , 10 ). In addition, the absence of a staging system with clinical and pathological features will also lead to a dilemma in treatment algorithm and prognostic assessment.…”
Section: Introductionmentioning
confidence: 99%